Mass balance of Phosphorus and Iron at the WWTP of Moni- Limassol and Phosphorus recovery from sludge - Κωνσταντινίδης, Βίκτωρας (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, 2016)
Proper and effective control of parameters inventory within each unit process of a wastewater treatment plant (WWTP) is the most important technique that can be used by plant operating staff to control the process. Control of parameters inventory has a direct effect on plant performance, process capacity, and system operating cost. It is the essential first step in optimizing the WWTP Mass balances around individual unit processes in a WWTP can be combined to produce a detailed mass balance for the entire WWTP. The output of one individual unit process becomes the input for the next downstream unit process. Multiple unit process mass balances can be used to estimate an input or output of a conservative process if few measurements are available. For example, the phosphorus or iron returned to a unit process from a recycle stream can be estimated in the absence of many data, and this estimate may highlight the need to undertake additional sampling or flow measurement of the recycle steam. The present postgraduate thesis aims thru analyses to produce the mass balance of phosphorus and iron for the entire WWTP. Having done that to examine the possible methods and best stage from where the recovery of phosphorus will be beneficial. Towards this scope four different scenarios were examined.
Keywords: Mass balance; Limassol WWTP; Phosphorus; Iron; Sampling; Recovery; Ισοζύγιο μάζας; ΜΒΕΛ Λεμεσού; Φωσφόρος; Σίδηρος; Δειγματοληψία; Εκχύλιση